Tarkovsky’s Philosophy of Love: Agape in Stalker and Sacrifice - Azgın, Bilge (Journal of History Culture and Art Research, 2018)
This article explores how the main characters in Tarkovsky’s movies Stalker and Sacrifice exhibit the Christian ideals of agape. With the New Testament, agape acquired metaphysical primacy and distinctive meaning as it came to be identified as originating from God and portraying a sacrificial act exemplified by the crucifixion of Jesus. Hence, agape necessarily entailed strong altruistic ethos and passionate commitment for the well being of others. Besides demonstrating the way in which Tarkovsky’s main heroes in Stalker and Sacrifice exhibit the ideals of agape while each going through their own unique “hero’s journey”, the article also seeks to unravel how Tarkovsky’s philosophy of love goes beyond mere “religious obstructionism”. Although Zizek argues that Tarkovsky’s ultimate message and solution to the ills of human existence is “religious obstructionism; that of self-sacrifice”, Tarkovsky’s philosophy of love provides much more complex and profound picture by entailing mystical characteristic and spiritual depth. Indeed, if one removes its metaphysical dimension, Tarkovsky’s philosophy of love may even align with the secular tempered existentialist and humanist tradition.